Psikoedukasi Stres Anak untuk Orang Tua: Penguatan Dukungan Emosional dalam Lingkungan Keluarga - Hardika , Jelang; Rinaldi, Martaria Rizky (Welfare : Jurnal Pengabdian Masyarakat, 2025)
Efforts to enhance responsive parenting literacy are increasingly essential, given the high prevalence of stress among children and the influential role of parental psychological conditions and caregiving quality. This community service program aimed to provide psychoeducation for parents affiliated with the Yogyakarta City Library and Archives Office regarding childhood stress, its contributing factors, behavioral indicators, and positive parenting– based coping strategies. The program was delivered online via Zoom and consisted of a pretest, material presentation, discussion session, and posttest. A total of 36 parents completed the pretest and 30 completed the posttest. Results indicated a notable increase in participants’ knowledge scores, demonstrating improved parental understanding of childhood stress and adaptive responses. These findings align with prior studies showing that psychoeducation enhances parenting knowledge, skills, and parental confidence. The program not only raised awareness of stress indicators in children but also strengthened parents’ capacities in providing a more supportive caregiving environment.